Addressing environmental challenges through spatial planning - Hussain, Athar 1976-; Tiwari, Kailash Chandra 1964-; Gupta, Alpana 1996- (Advances in geospatial technologies (AGT) book series, 2022)
This edited book is devoted to addressing environmental concerns and technology innovations in domains such as pollution, water insecurity and resources management, loss of green cover, energy efficiency, reducing carbon footprint, climate change, and disaster management with an aim to bridge the gap between engineering considerations and spatial aspects of planning.